A Strong Cutting Plane/Branch-and-Bound Algorithm for Node Packing - Nemhauser, G. L.; Sigismondi, G. (The Journal of the Operational Research Society, 1992)
We present a strong cutting plane/branch-and-bound algorithm for node packing. The cutting planes are obtained from cliques and lifting odd hole inequalities. Computational results are reported.